The role prescriptions of women leaders to achieve competitive advantage - Meldawati, Lucyani; Amalia, Fisy; Furqan, Andi Chairil; Faliza, Nur; Yuwanda, Tonny (Universitas Negeri Surabaya, Indonesia, 2023)
This study examines the differences between male and female leadership in the SMEs sector. It investigates the influence of innovative work behaviour preceded by psychological empowerment on competitive advantage in each dimension. This study uses a quantitative approach to distribute questionnaires to 254 Indonesian SMEs. Path analysis was used in this study by calculating factor loading, composite reliability, Average Variance Extracted (AVE), discriminant validity, and the structural model. To analyse the differences between female and male entrepreneurs, this study employs multi-group analysis, which can explain the phenomenon of this research. These findings explain that psychological empowerment has been found to increase innovative work behaviour, and innovative work behaviour has also been found to mediate the relationship between psychological empowerment and dimensions of competitive advantage. In addition, female leadership is superior in terms of time to market, where innovative employees led by a woman will develop new products faster to enter the market. On the other hand, male leadership is superior in the delivery dependability dimension, where innovative employees led by a man prioritise speed and responsiveness in serving customers.